2017
DOI: 10.1177/0194599817745269
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Status, Race and Insurance Status with Chronic Rhinosinusitis Patient‐Reported Outcome Measures

Abstract: Objective Disparities in health and health care access are widely prevalent. However, disparities among patients with chronic rhinosinusitis (CRS) are poorly understood. We investigated if CRS severity at presentation according to socioeconomic factors. Study Design Cross-sectional study. Setting Tertiary rhinology center. Subjects and Methods Three hundred prospectively recruited patients presenting with CRS were included. Outcome variables included CRS symptomatology, as reflected by the 22-item Sinonasal Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Our results showed that male gender and higher mean age were associated with lower (better) preoperative SNOT‐22 total scores. Even though the current study population and the population evaluated by Bergmark et al . are lacking some generalizability due to baseline QOL status and differences in treatment modality, our preoperative findings (Table ) are similar to those of Bergmark et al., who found no significant associations between race/ethnicity, zip code–based income, education level, or insurance status and mean baseline SNOT‐22 score or the EuroQol 5‐dimensional visual analogue scale, among patients with CRS presenting to a tertiary care center.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results showed that male gender and higher mean age were associated with lower (better) preoperative SNOT‐22 total scores. Even though the current study population and the population evaluated by Bergmark et al . are lacking some generalizability due to baseline QOL status and differences in treatment modality, our preoperative findings (Table ) are similar to those of Bergmark et al., who found no significant associations between race/ethnicity, zip code–based income, education level, or insurance status and mean baseline SNOT‐22 score or the EuroQol 5‐dimensional visual analogue scale, among patients with CRS presenting to a tertiary care center.…”
Section: Discussionsupporting
confidence: 83%
“…Even though the current study population and the population evaluated by Bergmark et al . are lacking some generalizability due to baseline QOL status and differences in treatment modality, our preoperative findings (Table ) are similar to those of Bergmark et al., who found no significant associations between race/ethnicity, zip code–based income, education level, or insurance status and mean baseline SNOT‐22 score or the EuroQol 5‐dimensional visual analogue scale, among patients with CRS presenting to a tertiary care center. Additionally, the finding in the current study that male subjects reported lower (better) preoperative SNOT‐22 scores compared to female patients is consistent with prior work …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Factors related to the medications, such as the complexity of the regimen, its side effects, or its costs, are also associated with adherence, which is consistent with the suggestion of our results that the use of intranasal corticosteroid sprays over irrigations may be associated with greater adherence. Other social factors, such as healthcare access, socioeconomic factors, and patient education, have also been described, although we did not study these characteristics because we previously found our patients to be quite homogeneous with respect to these characteristics . However, it is very likely that social factors may also have an impact on adherence with CRS medications …”
Section: Discussionmentioning
confidence: 96%
“…Other social factors, such as healthcare access, socioeconomic factors, and patient education, have also been described, although we did not study these characteristics because we previously found our patients to be quite homogeneous with respect to these characteristics. 23 However, it is very likely that social factors may also have an impact on adherence with CRS medications. 10,24 This study should be interpreted in the context of its limitations.…”
Section: Discussionmentioning
confidence: 99%